A call for industry specialization: an academic perspective on the importance of qualitative research - Krukowski, Kipp A., author; White, Lawrence Justin, Jr., author; The Value Examiner, publisher (Colorado State University. Libraries, 2021)
The purpose of this article is to highlight the advantages of specialization in business valuation. Industry specialists have the ability to craft the most insightful questions about a subject company and to understand the corresponding impact on value. We do not attempt to identify which industries or situations warrant the use of a specialist, or who should make that determination. Rather, we challenge the valuation industry to collectively develop a standard for when a specialist is needed.
Removed from view at request of the author.
Keywords: business valuation; business success; qualitative research; business planning; international competition; accounting standards